1993
DOI: 10.1021/bi00090a018
|View full text |Cite
|
Sign up to set email alerts
|

Role of electrostatic interactions in the binding of fluorescein by anti-fluorescein antibody 4-4-20

Abstract: Anti-fluorescein antibodies are excellent model systems for studying the biochemical basis of molecular recognition because a prodigious amount of both physico-chemical and structural information is available for these antibodies. Furthermore, recombinant single-chain antibodies have been produced for several anti-fluorescein antibodies, and site-specific mutagenesis studies have defined the energetic contributions of a number of key active-site residues. In previous studies, we determined the three-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…1 A). Electrostatic steering of fluorescein into the binding pocket (23,24) is evidenced by the salt dependence of k ass . The association rate constant of 4 M5.3 is Ï·14-fold lower than that of 4-4-20 scFv in both PBS and LSB.…”
Section: Resultsmentioning
confidence: 99%
“…1 A). Electrostatic steering of fluorescein into the binding pocket (23,24) is evidenced by the salt dependence of k ass . The association rate constant of 4 M5.3 is Ï·14-fold lower than that of 4-4-20 scFv in both PBS and LSB.…”
Section: Resultsmentioning
confidence: 99%
“…The Ab 4-4-20 is particularly useful in this regard, as it binds to the chromophore fluorescein (FLU) with high affinity (8). Interaction of 4-4-20 with FLU has greatly facilitated structural, kinetic and, thermodynamic characterization of this Ab (9)(10)(11)(12). Romesberg and colleagues (13)(14)(15) have characterized evolution of the immunological response for the well studied 4-4-20.…”
mentioning
confidence: 99%
“…This structure revealed that there were two tryptophan residues in intimate contact with the fluorescein moiety, either of which could participate in formation of a charge transfer complex. Nevertheless, a recent study by Omelyanenko et al (1993) showed that other factors are also involved in the quenching of fluorescein, including the local pH of the antigen-combining site and the formation of a salt link with a buried arginine residue. Several other physicochemical parameters of the antifluorescein system have been investigated using fluorescence quenching.…”
Section: 32b Fluorescence Quenchingmentioning
confidence: 99%